Dual chains competition under two recycling modes based on system dynamics method - Xue, R.; Zhang, F.; Tian, F.; Oloruntoba, Richard; Miao, S. (MDPI, 2018)
The fast-growing accumulation of electronic waste (e-waste) around the world is resulting in environmental pollution and adverse human health and, thus, has become a global area of concern. As the world's second largest producer of e-waste, China suffers significant pollution from e-waste because of inefficient recycling and management. This paper is a comparative systems dynamics study of two big home appliance manufacturers in China: Haier (Haier Group of Qingdao, China) and Gree (Gree Electric Appliances Inc. of Zhuhai, China). We used systems dynamics modeling to examine and compare the impact of closed-loop supply chain recycling and remanufacturing strategies on the total revenue of the supply chain and market shares of both manufacturers. Results show that an increase in third party service coverage and increased environmental awareness enhanced the total revenue of supply chain. Retailers showed more enthusiasm for recycling through contract development with manufacturers, thus resulting in reduced time of payment in closed-loop supply chains. We also found that an improvement of the recycling mechanism of retailers results in an increase in the share of the supply chain market. Hence, we propose a better supply chain mode.